Measurement Moslem religion in consumer behavior - Aflit Nuryulia Praswati; Tulus Prijanto (Jurnal Ekonomi & Keuangan Islam, 2017)
AbstractMost of the Indonesian population embraced Islam. The need and demand for products and services that meet the requirements and requirements of Islamic law are increasing. Indonesia is one of the 5 leading pioneer countries of ASEAN. The largest Muslim population is also in Indonesia. It is important for entrepreneurs, whether small, medium or large enterprises, need to understand how Muslim consumption behavior. A good understanding of Muslim consumption behavior can be a great opportunity to win the competition in the ASEAN Economic Community market. This study aims to analyze the measurement of Islamic religious community by taking into account consumption behavior. Data collection method used in this research is purposive sampling. The number of respondents in this study is 300 Muslim respondents. The results of this study of Muslim consumer behavior conclude that religion plays a very important role in making purchasing decisions from Indonesian Muslim society. The recommendation of this research is the need to create a conducive situation for Indonesian Muslim entrepreneurs in creating halal certified products and services to meet the needs of domestic and foreign markets. This form of support can be a business coaching workshop or the ease of lending capital from government or sharia financial services.